2014
DOI: 10.1007/s00775-014-1141-6
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium as a chemoprotectant: effect of vanadium(III)-l-cysteine complex against cyclophosphamide-induced hepatotoxicity and genotoxicity in Swiss albino mice

Abstract: Vanadium is an essential micronutrient for living systems and has antioxidant and genoprotective property. In the present study, the protective role of an organovanadium compound vanadium(III)-L-cysteine (VC-III) was evaluated against hepatotoxicity and genotoxicity induced by cyclophosphamide (CP) (25 mg/kg b.w., i.p.) in Swiss albino mice. Treatment with VC-III (1 mg/kg b.w., p.o.) mitigated CP-induced hepatic injury as indicated by reduction in activities of alanine transaminase, aspartate transaminase, alk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 58 publications
3
22
0
Order By: Relevance
“…Histological changes including liver congestion, disorganization of hepatic cords and ballooning degeneration could be observed in H&E slides. At the same time we have found a remarkable decrease in body weight gain after mice being treated with CTX, notably in high dose group, implying that hepatotoxicity might have contributed to this weight loss as previously reported (King and Perry, 2001;Basu et al, 2014). In addition, we also discovered that the expression level of apoptosis-related protein caspase-3 increased in the liver of mice after received CTX.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Histological changes including liver congestion, disorganization of hepatic cords and ballooning degeneration could be observed in H&E slides. At the same time we have found a remarkable decrease in body weight gain after mice being treated with CTX, notably in high dose group, implying that hepatotoxicity might have contributed to this weight loss as previously reported (King and Perry, 2001;Basu et al, 2014). In addition, we also discovered that the expression level of apoptosis-related protein caspase-3 increased in the liver of mice after received CTX.…”
Section: Discussionsupporting
confidence: 87%
“…In fact, research has shown that liver toxicity induced by CTX might be associated with the following mechanisms. CTX is extensively metabolized by the liver cytochrome P450 system, which probably causes sinusoidal obstruction syndrome, resulting in a direct toxic effect on hepatic sinusoidal cells, thus inducing necrosis, obstruction, and obliteration of hepatic veins (de Jonge et al, 2006;Basu et al, 2014). Kebieche et al (2009) investigated for the first time the implications of oxidative stress in liver toxicity induced by EPI via evaluating the redox status in hepatic cells in EPI-treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…Vanadium compounds have not only been studied as antidiabetic and insulinomimetic agents, but also for the treatment of parasitic diseases of tropical origin, for cancer and as protectors of tissue damage induced by chemical agents and oxidative stress [2,5,[175][176][177][178][179]. Some vanadium compounds, such as vanadylsulphate, sodium vanadate and peroxidovanadates have shown antitumor activity in experimental models in vitro and in vivo [177][178][179][180][181][182].…”
Section: Bioinorganic Implication and Application Of Vanadium Complexesmentioning
confidence: 99%
“…Acrolein, a toxic metabolite of CP, is responsible for chemically alkylate DNA as well as protein, producing cross-links and thereby inducing cytotoxicity [3]. Experimental evidence suggests that the development of oxidative stress after CP administration leads to decrease in the activities of antioxidant enzymes and increase in lipid peroxidation (LPO) level in liver and lungs of mice [4,5]. In addition, increased ROS production subsequently leads to activation of cells of pulmonary defense system like neutrophils, monocytes, and macrophages causing pulmonary fibrosis [6].…”
Section: Introductionmentioning
confidence: 99%